Exploring ancient cities Crete, Petra, Pompeii, Teotihuacan (San Francisco : Sumeria, 1994)
Describe on the ancient cities and focusses on Crete, Petra, Pompeii and Teotihuacan
System requirements: 486 or higher, 33MHz processor, 8MB RAM, DOS 5.0, Windows 3.1 or 95, VGA+ display, sound card, double-speed CD-ROM drive
Keywords: Greece -- Antiquities; Crete (Greece) -- History; Petra (Ancient city) -- History; Pompeii (Ancient city) -- History